Affecting processing and properties of injection moulded thin-wall parts using dynamic tempered rapid tooling moulds - Drummer, Dietmar; Meister, Steve; Wildner, Wolfgang (Zeitschrift Kunststofftechnik, 2016)
Keywords: Mechanical properties; Morphology; Orientations; Thin wall injection moulding; Variothermal mould tempering

A fiber optic temperature sensor based on the combination of epoxy and glass particles with different thermo-optic coefficients - Wildner, Wolfgang; Drummer, Dietmar (Photonic Sensors, 2016)
This paper describes the development and function of an optical fiber temperature sensor made out of a compound of epoxy and optical glass particles. Because of the different thermo-optic coefficients of these materials, this compound exhibits a strong wavelength and temperature dependent optical transmission, and it therefore can be employed for fiber optic temperature measurements. The temperature at the sensor, which is integrated into a polymer optical fiber (POF), is evaluated by the ratio of the transmitted intensity of two different light-emitting diodes (LED) with a wavelength of 460 nm and 650 nm. The material characterization and influences of different sensor lengths and two particle sizes on the measurement result are discussed. The temperature dependency of the transmission increases with smaller particles and with increasing sensor length. With glass particles with a diameter of 43 extgreekmm and a sensor length of 9.8 mm, the intensity ratio of the two LEDs decreases by 60% within a temperature change from 10℃ to 40℃.
UnivIS-Import:2017-01-09:Pub.2016.tech.FT.FT-KT.afiber
Keywords: epoxy; fiber optic sensors; glass particles; Temperature sensors; thermo-optic coefficient

A Fiber Optic Temperature Sensor Based on the Combination of Two Materials with Different Thermo-Optic Coefficients - Wildner, Wolfgang; Drummer, Dietmar (IEEE Sensors Journal, 2016)
The design and development of a plastic optical fiber (POF) temperature sensor is presented: By combining two materials with different thermo-optic coefficients (in this case: a transparent oil or polymer and glass-particles) in a compound, a temperature dependent transmission can be achieved. With the use of more than one light source with different wavelengths, a spectrometer for the analysis of the measurement is no longer necessary.
UnivIS-Import:2016-02-10:Pub.2015.tech.FT.FT-KT.afiber

Analysis of the processing-pressure dependent refractive index of polycarbonate by transmission measurements of glass-filled specimen - Roth, Benedikt; Wildner, Wolfgang; Drummer, Dietmar (Polymer Engineering and Science, 2019)

Analysis of the processing-pressure dependent refractive index of Poly(methyl methacrylate) by transmission measurements of glass-filled specimen - Wildner, Wolfgang; Drummer, Dietmar (Polymer Testing, 2018)

Compression-Induced Solidification: A Novel Processing Technique for Precise Thermoplastic Optical Components with Negligible Internal Stresses - Jungmeier, Ariane; Wildner, Wolfgang; Drummer, Dietmar; Kühnert, Ines (ISRN Optics, 2012)
UnivIS-Import:2015-03-09:Pub.2012.tech.FT.FT-KT.compre

Compression-Induced Solidification - Roth, Benedikt; Wildner, Wolfgang; Drummer, Dietmar (Polymers, 2020)

Druckverfestigung: Übertragung der Grundlagen auf die Spritzgießvariante - Wildner, Wolfgang; Drummer, Dietmar; Kühnert, Ines (VDI-Fachkonferenz, 2012)
UnivIS-Import:2015-04-16:Pub.2012.tech.FT.FT-KT.druckv

Dynamic compression induced solidification - Roth, Benedikt; Wildner, Wolfgang; Drummer, Dietmar (Polymers, 2020)
This study presents a method for the determination of the dynamic pressure-dependent solidification of polycarbonate (PC) during flow using high pressure capillary rheometer (HPC) measurements. In addition, the pressure-dependent solidification was determined by isothermal pressure-volume-temperature (pvT)measurements under static conditionswithout shear. Independent of the compression velocity, a linear increase of the solidification pressure with temperature could be determined. Furthermore, the results indicate that the relaxation time at a constant temperature and compression rate can increase to such an extent that the material can no longer follow within the time scale specified by the compression rate. Consequently, the flow through the capillary stops at a specific pressure, with higher compression rates resulting in lower solidification pressures. Consequently, in regard to HPC measurements, it could be shown that the evaluation of the pressure via a pressure hole can lead to measurement errors in the limit range. Since the filling process in injection molding usually takes place under such transient conditions, the results are likely to be relevant for modelling the flow processes of thin-walled and microstructures with high aspect ratios.
CRIS-Team Scopus Importer:2020-03-17
Keywords: No-flow pressure; Polycarbonate; Solidification

Kunststoffe in Optischen Systemen - Drummer, Dietmar; Ranft, Florian; Wildner, Wolfgang (Kunststoffe, 2012)
UnivIS-Import:2015-03-09:Pub.2012.tech.FT.FT-KT.kunsts

Light scattering and optical performance of glass-particle filled matrices with similar refractive index - Wildner, Wolfgang; Drummer, Dietmar (Journal of Composite Materials, 2018)
EAM Import::2019-03-12

Light scattering of glass-particle filled matrices with similar refractive index - Wildner, Wolfgang; Drummer, Dietmar (Journal of Composite Materials, 2018)
If fillers can be added to transparent materials without losing transparency, then advantages like enhanced mechanical and thermal properties can be integrated. The investigated specimens consist of glass particles and refractive index oil as a model for transparent matrices with a very similar refractive index. Their optical properties and resulting limitations are described. Potential uses are also demonstrated by application-oriented optical testing. Besides a standard spectrometer, additional spectrometer setups were used. These include a diffuse as well as a collimated illumination and different sample positioning. Furthermore, the scattered light intensity was measured at different angles. This analysis reveals that composites with smaller particles transmit more light directly. In contrast, standard spectrometers indicate an increasing direct transmittance of composites with larger particles. They collect significant amounts of scattered light and, therefore, are not suitable for transmission measurements of such composites. The different positioning shows that all specimens exhibit very little scattering when placed directly on a diffuse light source. With a greater distance between specimen and light source, the scattering increases strongly. To display the composites' optical appearance, the light-dark-contrast of the diffuse white light source photographed behind the composite was analyzed. Both long and short distances between composite and light source lead to a precise image of the light source. Nevertheless, the white light source appears in the color of the wavelength with matching refractive indices at long distances.
Keywords: light scattering; Glass particles; optical compound

Modelling haze and transmission of transparent filled systems in dependence of filler surface area, refractive index difference and wavelength - Wildner, Wolfgang; Drummer, Dietmar (SPE Proceedings ANTEC, 2015)
Glass-filled polymers with a matching refractive between polymer and glass might combine transparency. In this paper the transparency of glassfilled polymers transparency and haze, model-like specimens consisting out of a cuvette filled with oil and glass fillers were prepared. The haze of these specimens is strongly dependent on the refractive index difference between oil and filler material and is close to zero at a matching refractive index. On the basis of these measurements an empirical model for the calculation of transparency and haze is created. The results provided by this model show a good match with the measured values of the specimens and also with results of experiments described in literature. Based on the model, calculated graphs to determine the haze of glass-filled polymers in dependence of the specific filler surface area, the refractive index difference, the wavelength and the sample thickness.
UnivIS-Import:2015-10-26:Pub.2015.tech.FT.FT-KT.modell_3

Nano Filler Materials for Transparent Polymer Composites: Influences on the Properties and on the Transparency — A review - Wildner, Wolfgang; Drummer, Dietmar (Polymer Composites, 2016)
EAM Import::2019-03-12

Nanofiller materials for transparent polymer composites: Influences on the properties and on the transparency—A review - Wildner, Wolfgang; Drummer, Dietmar (Journal of Thermoplastic Composite Materials, 2018)
Filler materials are widely used in combination with polymer materials. Conventional filler particles generally cause light scattering and absorption because of their optical characteristic or refractive index difference. With nanoparticles (NPs) as a filler material, it is theoretically possible to manufacture transparent compounds due to their small particle dimensions reducing the interaction with light. Nevertheless, the particles tend to build agglomerates and aggregates which reduce the composite's transparency considerably. This review gives an overview of the effect different particle materials have on the properties of transparent polymer composites with consideration of the composite's transparency. There are very few reports on highly transparent and thick (>1 mm) polymer nanocomposites with such an amount of particles that affect other properties of the polymer significantly. In the majority of cases, NPs lead to a significant lower transparency. This indicates that the homogeneous dispersion of the particles is still a major difficulty in producing transparent nanocomposites with enhanced properties.

Plastics in Optical Systems - Drummer, Dietmar; Ranft, Florian; Wildner, Wolfgang (Kunststoffe International, 2012)
UnivIS-Import:2015-03-09:Pub.2012.tech.FT.FT-KT.plasti

Prozess- und Eigenschaftsbeeinflussung dünnwandiger Spritzgießteile mittels dynamisch temperierten Rapid Tooling Spritzgießwerkzeugen - Drummer, Dietmar; Meister, Steve; Wildner, Wolfgang (Zeitschrift Kunststofftechnik, 2016)
UnivIS-Import:2016-06-01:Pub.2016.tech.FT.FT-KT.prozes

The mechanical and optical properties of injection-moulded PMMA, filled with glass particles of a matching refractive index - Wildner, Wolfgang; Drummer, Dietmar (Polymers and Polymer Composites, 2017)
In this paper, the optical and mechanical properties of injection-molded plates (thickness: 1 mm) made of poly(methyl methacrylate) (PMMA) and glass particles as filler with a matching refractive index are investigated. Tests show that the orientation resulting from the injection molding process greatly affects the tensile strength and elongation at break, whereas the elastic modulus merely depends on the filling degree, which is investigated up to 13 vol.%. In terms of the optical properties, the specimens' haze depends on the difference in the refractive index between a glass and polymer. However, the absolute value of haze increases with an increasing filling degree and a decreasing particle size. Surface defects resulting from the injection molding process were found to be the primary reason for this haze even with identical RI between PMMA and glass.

Trend report: Plastics in optical systems - Drummer, Dietmar; Ranft, Florian; Wildner, Wolfgang (Kunststoffe International, 2012)

Wavelength Dependent Haze of Transparent Glass-Particle Filled Poly(Methyl Methacrylate) Composites - Wildner, Wolfgang; Drummer, Dietmar (ISRN Optics, 2014)
Glass particles as filler were incorporated in a poly(methyl methacrylate) matrix. The refractive indexes of both materials match at a wavelength of about 400 nm. The effect of particle volume fraction on the light transmittance and light scattering (haze) in dependence of the refractive index difference was studied. The curve shape of the haze in dependence of the wavelength is comparable to that of the refractive index difference, but the base line of the haze increases with the filling grade. This indicates that there are other scattering or absorbing mechanisms, like defects in the filler binding.
UnivIS-Import:2015-03-09:Pub.2014.tech.FT.FT-KT.wavele